PENGARUH KESEJAHTERAAN PETANI KARET TERHADAP PENDIDIKAN ANAK DI DESA TERATAK AIR HITAM KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Agra Nurharisman; Almasdi Syahza; Rina Selva Johan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the influence of the welfare of rubber farmers to the education of children in the village of Teratak Air Hitam Sentajo Raya Sub-district Kuantan Singing District. The subjects of this study are farmers who have childrens that droped out from school. The total sample are 41 respondents using the method of Proposive Sampling. The data used for this study are primary data collected by using questionnaires and documentation. Data analysis technique used the chi square test analysis. The results of this study indicate that the, rubber farmers are prosperous it can be seen from the fulfillment of welfare indicators. On the other hand the education of children of rubber farmers is still low. This study found that there is no significant relationship between the rubber farmer’s welfare and their children's education in the village of Teratak Air Hitam Sentajo Raya Sub-district Kuantan Singingi Regency.Keywords: Rubber Farmer's Welfare, Children's Education.